Biological and economic evaluation of new samples of sweet corn on Ustymivka Experimental Station of Plant Production - Харченко, Ю. В.; Харченко, Л. Я.; Клімова, О. Є. (Scientific Progress & Innovations, 2016)
We clarified the potential of inbred lines of sweet corn by productivity and its components in conditions of Forest-Steppe zone of Ukraine. We revealed samples with varying degrees of environmental adaptation, that allows the execution to create an environmentally-oriented hybrid programs. According to the results of research we highlighted valuable genotypes for practical breeding and we offered the ways of their future use in heterosis breeding of this subspecies of corn.